Critique of Latin American Pedagogy in Fernando González - Pérez Restrepo, Thomas (Escritos, 2026)
This essay examines the pedagogical thought of Colombian philosopher Fernando González Ochoa as a critique of Latin American educational models from the first half of the 20th century, which imitated European forms and denied local realities. Through works such as Los negroides and El maestro de escuela, he establishes a key distinction: instruction is seen as domestication and vanity, while cultivation focuses on the development of personality. His proposal is articulated around three central axes: egoence (self-expression and vital energy) as a teleological end; the redefinition of the teacher as a midwife (maieutics) who guides discovery rather than transmitting facts; and the emotional method based on direct experience. González’s pedagogy is presented as a project of epistemic and ontological decolonization. Its objective is to overcome the Latin American subject’s sense of illegitimacy in order to achieve authenticity and cosmic consciousness.